2019
DOI: 10.4143/crt.2018.513
|View full text |Cite
|
Sign up to set email alerts
|

Higher Age Puts Lung Cancer Patients at Risk for Not Receiving Anti-cancer Treatment

Abstract: Purpose We aimed to determine the demographic and epidemiologic variables that are associated with no treatment in lung cancer patients. Materials and Methods Patient data were collected from the Korean National Health Insurance Database. The lung cancer group included patients with an initial diagnosis of lung cancer between January 2009 and December 2014. Treated cases were defined as those that underwent surgery, radiation, or chemotherapy until death, after the diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The univariate and multivariate logistic analysis indicated that age, AHI, TNM stage, cancer types, BMI and ODI4 were risk factors for overall survival. Studies confirmed that age is an important factor in the occurrence of lung cancer and as an independent risk factor for survival and prognosis of lung cancer patients (19). The continuous increase of obstructive sleep apnea with age challenges the current theory that mortality due to obstructive sleep apnea and cardiovascular co-morbidities affect obstructive sleep apnea prevalence at an advanced age (20).…”
Section: Discussionmentioning
confidence: 99%
“…The univariate and multivariate logistic analysis indicated that age, AHI, TNM stage, cancer types, BMI and ODI4 were risk factors for overall survival. Studies confirmed that age is an important factor in the occurrence of lung cancer and as an independent risk factor for survival and prognosis of lung cancer patients (19). The continuous increase of obstructive sleep apnea with age challenges the current theory that mortality due to obstructive sleep apnea and cardiovascular co-morbidities affect obstructive sleep apnea prevalence at an advanced age (20).…”
Section: Discussionmentioning
confidence: 99%
“…This database was described earlier [ 13 ]. Briefly, this study used data from the National Health Insurance Service-National Sample Cohort (NHIS-NSC) 2002 to 2015, released by the NHIS in 2015, which includes all medical claims filed from January 2002 to December 2015 for 1,031,392 nationally representative randomly selected patients, accounting for approximately 2.2% of the entire population of the NHIS in 2002.…”
Section: Methodsmentioning
confidence: 99%